Seamounts and related topographic highs – automated mapping in support of sustainable ocean management, Norway - Dolan, Margaret F. J.; Bjarnadóttir, Lilja R. (Frontiers in Earth Science, 2025)
Seamounts are a prime example of an ecologically relevant marine landform. They are internationally recognized by the OSPAR commission as a threatened and/or declining habitat yet estimates of their distribution in Norwegian waters are not adequately reported in databases used for ocean management. Here we describe mapping of the distribution of seamounts and related topographic highs, conducted for Norway’s offshore seabed mapping program MAREANO. We employ a combination of automated methods to detect, delineate and characterize peaks and associated areas of elevated terrain from the GEBCO global bathymetry data compilation. The resulting broad-scale (1:2,000 000) map includes seamounts (over 1,000 m high), lower knolls and mounds as well as many ridges, several of which are of comparable height to seamounts. Our results include hundreds of topographic highs not reported by previous studies as well as confirming and further characterizing many known features through geomorphometric analysis. This new information contributes to documentation of seabed geodiversity and provides timely data for international reporting and knowledge-based ocean management supporting sustainable development of offshore resources, following SDG14 (Life Below Water). The maps serve as baseline information for further scientific studies, including characterization of the associated benthic habitats which will ultimately help define appropriate management measures.